Potassium Dichromate Impact on Male Reproductive Integrity Biomarker in Rat. Two Generation Study - Jelena Rankov; Adriana Trif; Diana Brezovan; Florin Muselin (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this study was the evaluation of Cr VI cumulative and differentiate exposure on integrity biomarker of male reproductive system. The objective was evaluation of potassium dichromate intake on genital organs and sexual accessory glands architecture in male rats from two generation. Males and females from F0 generation were exposed to potassium dichromate three months before mating. F1 generation was represented by male pups, resulted from F0 generation, exposed to potassium dichromate in utero, during suckling (via milk and water) period and until sexual maturity.  All the animals were divided in one control and three experimental groups, exposed to Cr VI trough drinking water, as followed E1: 25 ppm (LOAEL); E2: 50 ppm: E3: 75 ppm; control group received tap water without chromium content. The experiment was carried out with respecting legislation regarding ethics in animal experiments. The study revealed the presence of congestive and degenerative lesions in genital organs and sexual accessory glands of exposed individuals from F0 and F1 generation such as: interstitial edema, epithelial necrosis and atrophy, membrane exfoliation and necrosis. The lesions frequency and intensity were directly correlated to exposure level, the most affected being E3 group and generation, more pronounced in F1 generation.